2019
DOI: 10.1002/pon.5045
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with a psychosocial screening instrument (S‐FIRST) to identify the psychosocial support needs of parents of children suffering from cancer

Abstract: Objectives:A large proportion of families with a child suffering from cancer are heavily burdened, both psychologically and socially functions, thus requiring treatment. Therefore, a systematic assessment of burden and needs is essential to identify clients with a high psychosocial burden and to allow for accurate decision making regarding indications for treatment. There is a great need for the development and validation of screening instruments in psychosocial counseling. Methods:The receiver operating chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…Most research on social support mainly focuses on analysing social support received. More specifically, studies have shown that support is a source that helps parents cope with the difficult situations caused by childhood cancer (Haunberger et al, 2019). However, social support provided by parents to other people facing the same situation is also a key variable to cope with such a difficult situation, as confirmed by the results from the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Most research on social support mainly focuses on analysing social support received. More specifically, studies have shown that support is a source that helps parents cope with the difficult situations caused by childhood cancer (Haunberger et al, 2019). However, social support provided by parents to other people facing the same situation is also a key variable to cope with such a difficult situation, as confirmed by the results from the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Most of the research on social support places its main focus on analyzing social support received, with few studies examining the influence that social support provided may have on parents' quality of life. Previous studies have shown that the social support received is a source of resources helping parents cope with the difficult situation of childhood cancer [68]. However, the social support that parents provide to their own network is also a fundamental variable in the management of this process, as the results of this study show.…”
Section: Discussionsupporting
confidence: 49%
“…In scientific discourse in the field of social work, there is an active debate on the development of suitable concepts and methods for case analyses (Buttner, Gahleitner, Hochuli Freund, & Röh, 2018;Gahleitner, Hahn, & Glemser, 2012). Some empirical studies on diagnostics in social work are available in the English-language literature, especially with regard to quantitative research in the areas of clinical social work (Harkness, 2011;Haunberger, Rüegger, & Baumgartner, 2019;Ishibashi, 2005) and child protection (e.g., Helm, 2011;Thomas & Holland, 2010). In contrast, in the German-language literature, only few empirical studies are available on diagnostics in social work in the area of public health (Gautschi & Rüegger, 2012;Hanses, 2002;Hüttemann, 2008;Wyssen-Kaufmann, 2015) and child protection (Becker-Lenz, Gautschi, & Rüegger, 2017;Rüegger, 2017).…”
Section: Diagnostics In Social Workmentioning
confidence: 99%
“…In a first step, we divided the population into two groups with the help of the S-FIRST screening instrument. A cut-off level (13-14) was calculated using the statistical part of S-FIRST (for details see Haunberger et al, 2019). On the basis of N = 71 cases (survey wave one), the screening divided the parents into a group with high psychosocial burden (56%, n = 31) and a group with low psychosocial burden (44%, n = 40).…”
Section: Effects Of Social Counselingmentioning
confidence: 99%